Identification and isolation of cinnamate 4-hydroxylase and chalcon syntase genes in the roots of scrophularia striata and study of their expression and some physiological traits under the influence of various abiotic elicitors - Zeinab Rostami; Arash Fazeli (مجله بیوتکنولوژی کشاورزی, 2021)
Objective Scrophularia striata is a plant belonging to the Scrophulariaceae family. Due to the importance of phenylpropanoid compounds in this plant, identification and isolation of genes encoding cinnamate enzymes 4-hydroxylase (C4H) and chalcone synthetase (CHS) involved in the biosynthesis of these compounds and also, their expression under the influence of various abiotic elicitors was performed. Materials and methods Seeds of wild plants grown around the university were collected and were cultured in greenhouse conditions. Sampling was done before flowering stage. RNA extraction, cDNA synthesis, isolation and sequencing of CHS and C4H genes in the roots of this plant were successfully performed for the first time. The expression of these genes was performed under the influence of three salicylic acid (SA), jasmonic acid (JA) and gibberellic acid (GA) each at concentrations of 100 and 300 ppm using a completely randomized design at the transcript level by Real Time PCR method.     Results The results showed that among the elicitors used, JA and SA with the concentration of 100 ppm had the greatest effect on increasing the expression of C4H and CHS genes so that in investigating the effect of the above-mentioned elicitors on the accumulation of phenylpropanoid compounds, this issue was partially confirmed. Also, in the study, increasing the concentration of JA and SA decreased the expression of C4H and CHS genes. Conclusions The general results of the use of elicitors on gene expression and accumulation of secondary metabolites showed that the external use of stimulants in appropriate concentrations, possibly through the induction of the plant immune system, can play a role in the biosynthesis and accumulation of valuable secondary metabolites such as phenylpropanoid compounds in the roots of Scrophularia striata and subsequently identifying and analyzing the expression of genes involved in the biosynthesis of such valuable compounds can be effective in complementary basic research for use in the pharmaceutical and food industries.